2015
DOI: 10.1136/acupmed-2014-010738
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture versus Usual Care for Postoperative Nausea and Vomiting in Children after Tonsillectomy/Adenoidectomy: A Pragmatic, Multicentre, Double-Blinded, Randomised Trial

Abstract: Objectives To investigate the effect of a standardised acupuncture on nausea and vomiting in children after tonsillectomy with or without adenoidectomy when possible placebo effects were precluded. Methods A pragmatic, multicentre, doubleblinded, randomised controlled trial. The study was conducted over 10 months in 2012-2013 at three ambulatory clinics. Two hundred and eighty-two children, age 1-11 years, American Society of Anesthesiologists grade ≤II, were included. To equalise expectancy effects, all paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 28 publications
(28 reference statements)
2
34
0
2
Order By: Relevance
“…Four studies reported the need for rescue medication 52,61,62 64,66 and five reported adverse events. 37,53,57,59,63 Discomfort and treatment satisfaction were reported twice. 37,59,60,62 Resumption to normal activity, complete response, emergence agitation, parent satisfaction, and recovery time were reported once each.…”
Section: Norheim Et Almentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies reported the need for rescue medication 52,61,62 64,66 and five reported adverse events. 37,53,57,59,63 Discomfort and treatment satisfaction were reported twice. 37,59,60,62 Resumption to normal activity, complete response, emergence agitation, parent satisfaction, and recovery time were reported once each.…”
Section: Norheim Et Almentioning
confidence: 99%
“…59 For maintenance anesthesia, ten studies used volatile anesthetics, 52,[54][55][56]58,60,[62][63][64][65] four studies used intravenous anesthetics, 57,59,61,66 a multicenter study included both volatile and intravenous anesthetics, 37 and in one study anesthesia was not specified. 53 The studies encompassed a range of types of surgery, including strabismus surgery, tonsillectomy, and laparoscopic cholecystectomy.…”
Section: Norheim Et Almentioning
confidence: 99%
See 3 more Smart Citations